Hubungan Pengetahuan Ibu dan Dukungan Suami dengan Penggunaan Kontrasepsi Intra Uterin Device - Turiyani, Turiyani (JOURNAL OF HEALTH SCIENCE, 2025)
Family planning is an action that helps individuals or married couples to achieve certain objectives, avoid unwanted births and regulate the interval between pregnancies. The use of the MKJP contraceptive method in active family planning in OKU Regency is still very low, namely the IUD method of 3.6%, MOP of 0.2%, MOW of 1.2% and implants of 11.2%. This type of research is quantitative using the Analytical Survey method with a Cross Sectional approach. This research was conducted in June 2021 at the UPTD Puskesmas Lubuk Batang in 2021. The population in this study were all 311 active family planning acceptors. The sample size of 76 people was determined by the Slovyn formula. The sampling technique of Non Random Sampling is accidental sampling. The analysis used is univariate analysis and bivariate analysis. The results of the Chi Square statistical test showed that there was a relationship between mother's knowledge and the use of IUD contraception with P Value = 0.039. There is a relationship between husband's support and the use of IUD contraception with P Value = 0.016. This study can expand the information obtained by the Puskesmas regarding the IUD, especially the characteristics of the acceptor and the factors that influence the selection of the IUD, so that each acceptor can use the right contraception according to his characteristics and needs. Keywords:Husband's support, Mother's knowledge, UseContraceptives, Intra Uterine